Will the Stop TB Partnership targets on TB control be realised on schedule? Projection of future incidence, prevalence and death rates. (2017) - Chang, Yu Sang; Choi, Changyong
World Health Organization (WHO) declared tuberculosis (TB) as a global emergency in 1993, and recommends the approach developed by the Stop TB Partnership. Targets set by the Partnership are as follows: by 2015, reduce prevalence and death rates by 50%, compared with their levels in 1990, and by 2050, eliminate TB as a public health problem, defined as a global incidence of active TB of less than one case per 1 million population per year. The basic objective of this study is to test whether these targets will be realised on schedule. We have selected 22 so-called high-burden countries that account for over 80% of the world's TB cases. For each country, we have developed a forecasting model based on experience curve for incidence, prevalence, and mortality rate. After projecting the future rates for 2015 and 2050, we compare our projections with the future targets set by the Partnership.